The mechanism of NDM-1-catalyzed carbapenem hydrolysis is distinct from that of penicillin or cephalosporin hydrolysis - Han Feng (Nature Portfolio, 2017)
New Delhi metallo-β-lactamases (NDMs) hydrolyze almost all β-lactam antibiotics and pose a major public health threat. Here, the authors study the mechanism of NDM-1 catalyzed carbapenem hydrolysis and present the crystal structures of the enzyme-intermediate and product complexes, which is important for drug design.